2023
DOI: 10.1136/ijgc-2023-004572
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node detection in early-stage ovarian cancer: a systematic review and meta-analysis

Abstract: BackgroundA systematic pelvic and para-aortic lymphadenectomy remains the surgical standard management of early-stage epithelial ovarian cancer. Sentinel lymph node mapping is being investigated as an alternative procedure; however, data reporting sentinel lymph node performance are heterogeneous and limited.ObjectiveA systematic pelvic and para-aortic lymphadenectomy remains the surgical standard management of early-stage epithelial ovarian cancer. Sentinel lymph node mapping is being investigated as an alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…In our meta-analysis, the pooled detection rate of SLNB in early-stage ovarian cancer was 94% (95% CI 86% to 100%, I 2 = 79%, p < 0.0001). This is in agreement with a recent meta-analysis on lymph node detection in early-stage ovarian cancer, which included nine studies and reported a detection rate of 93.3% per patient (95% CI 77.8% to 100%; I 2 = 74.3%, p < 0.0001) [38]. This is also comparable to the detection rates in other more well-established malignancies such as endometrial cancer, with a detection rate of 87%; breast cancer, with a detection rate of 97.9% with ICG; vulvar cancer, with a detection rate of 98% with blue dye and 99mTc radioisotope; and cervical cancer, with a detection rate of 98% with ICG [12,13,16,39].…”
Section: Discussionsupporting
confidence: 92%
“…In our meta-analysis, the pooled detection rate of SLNB in early-stage ovarian cancer was 94% (95% CI 86% to 100%, I 2 = 79%, p < 0.0001). This is in agreement with a recent meta-analysis on lymph node detection in early-stage ovarian cancer, which included nine studies and reported a detection rate of 93.3% per patient (95% CI 77.8% to 100%; I 2 = 74.3%, p < 0.0001) [38]. This is also comparable to the detection rates in other more well-established malignancies such as endometrial cancer, with a detection rate of 87%; breast cancer, with a detection rate of 97.9% with ICG; vulvar cancer, with a detection rate of 98% with blue dye and 99mTc radioisotope; and cervical cancer, with a detection rate of 98% with ICG [12,13,16,39].…”
Section: Discussionsupporting
confidence: 92%
“…In particular, the overall mean (per patient) SLN detection rate in case of ICG alone was reported to be 58.6% (99/169) [13 ▪▪ ] compared with 95% (57/60) in case of ICG + technetium [14 ▪▪ ,15 ▪ ], and with 52.9% (9/17) in case of technetium alone or in combination with blue dye [16 ▪ ,17 ▪ ] ( P < 0.001). Despite this difference, a recently published meta-analysis did not find a statistically significant difference in SLN detection rate when different tracers were compared, but a large heterogeneity between the included studies was reported [18 ▪ ]. Volume of tracer injection was also different across the studies, ranging from 0.2 ml to 2 ml per site of injection [13 ▪▪ ,14 ▪▪ ,15 ▪ ,16 ▪ ,17 ▪ ].…”
Section: Type Of Tracermentioning
confidence: 92%
“…More recently, indocyanine green (ICG) has been proposed to map SLN in OC after its large application in SLN detection in uterine cancers with demonstrated superiority when compared to other tracers [11,12]. Nevertheless, the use of ICG alone [13 ▪▪ ,14 ▪▪ ] has been associated with lower SLN detection rates compared with ICG + radioisotope [15 ▪ ,16 ▪ ] but similar to those obtained with radioisotope ± blue dye [17 ▪ ,18 ▪ ]. In particular, the overall mean (per patient) SLN detection rate in case of ICG alone was reported to be 58.6% (99/169) [13 ▪▪ ] compared with 95% (57/60) in case of ICG + technetium [14 ▪▪ ,15 ▪ ], and with 52.9% (9/17) in case of technetium alone or in combination with blue dye [16 ▪ ,17 ▪ ] ( P < 0.001).…”
Section: Type Of Tracermentioning
confidence: 97%
“…In this month's Lead Article, Agustí and colleagues describe their systematic review and meta-analysis aimed at evaluating the detection rate and diagnostic accuracy of sentinel lymph node biopsy mapping in patients with early stage ovarian cancer. 1 The study showed a 92% pooled detection rate and 100% negative predictive value of sentinel lymph node biopsy. In particular, the dual tracers, technetium-99 and indocyanine green, and dual site injection (utero-ovarian and infundibolo-pelvic ligament), gave optimal detection when injected before adnexectomy.…”
mentioning
confidence: 82%